The Shear Damage Model of the Two-Component Forming Polymer Grouting Material-Bentonite Contact Surface - Hao Zhang; Mingrui Du; Yan Zhao; Liangqiong Chen (Advances in Materials Science and Engineering)
The newly developed two-component polymer (TFPU) cut-off walls have great application potential in civil engineering for water-seepage prevention. Investigating the mechanical interactions between TFPU and soil from the theoretical perspective can provide a basis for furtherly evaluating the stability of TFPU cut-off walls, which, however, has not been conducted. In this study, based on the shear testing results, the shear damage model of the TFPU-bentonite contact surface was established. Studies show that the TFPU-bentonite contact surface performs strain-softening behavior under shear and that the strain-softening behavior becomes less and less obvious when the normal stress increases. The theoretical shear stress-strain curves are in good consistent with the experimental ones, and the maximum differences between the theoretical shear stress and shear strain at yield and the experimental ones are about 3.88% and 3.40%, respectively, indicating that the shear damage model can reflect the mechanical properties of the TFPU-bentonite contact surface. The critical damage of the contact surface increases from 0.05 to 0.50 in the power function way when normal stress increases from 75 to 1200 kPa, implying that the shear failure of the contact surfaces changes from brittleness to ductility. This study provides a theoretical base for evaluating the influences of the TFPU-soil contact surface on the stability of the TFPU cut-off wall structures.